Study the Effect of Baghdad City on the Tigris River Water Pollution - Al-Shemari, Hussain M.; Abdulhussain, Ihssan A. (Basrah Journal for Engineering Sciences, 2013)
Water pollution is the most important tasks facing all countries in the world to obtain suitable water for municipal, industrial, and agricultural uses. This study concerns with the effect of Bagdad city waste water on pollution and quality of Tigris River water using index of Aquifer water quality (IAWQ). The accuracy of chemical analyses of the selected water samples are conduced according to world standards of health classifications. Results of these analysis show that only two types of the 13th tested sample are ( certain ) ,while the other patterns ( models )are of the ( probable certain ). Cluster analysis is applied to evaluate the studied water characteristic. The results of the cluster analysis show the presence of three varying groups in their impact on their chemical properties on water .According to the cluster analysis and permissible limits of the variables, three chemical variables cadmium, lead, and calcium are selected to indicate its impact on the studied area. It is found that when using (IAWG) for the Tigris River, there is an increase in the values of the index along the river from its entry to Baghdad until it meets the Diyala river, showing a clear pollution of the Tigris river water.